Exploring Stakeholders Attitudes towards Digital Agricultural Communication and Services - Guntukougula Pattabhi, Sandeep; Sundaresan Ganesamoorthi; Kodagavallihatti Palaiah Raghuprasad; Vasappa Govinda Gowda; Palayyan Saraswathy Benherlal; Thavakadahalli Lakshminarasappa Mohan Kumar (Indian Journal of Extension Education, 2023)
Digital agricultural communication and services enhance agricultural production by delivering real-time data, information, and support to stakeholders, thereby substantially extending the reach and impact of agricultural extension. The study, conducted in 2023, encompassed all three Agro-Climatic Zones within Telangana and employed an ex post facto research design. Data collection involved personal interviews with a sample size of 180 farmers, 30 input dealers, 30 extension personnel, and 30 scientists. The study found that more than half (57.04%) of the overall sample expressed favorable attitudes toward digital agricultural communication and services. Mean attitude scores varied, with scientists scoring the highest (172.87), followed by farmers (169.23), extension personnel (166.37), and input dealers (165.23). Regression analysis using selected independent variables produced R2 values of 0.789 for farmers, 0.805 for input dealers, 0.720 for extension personnel, and 0.870 for scientists, indicating the effectiveness of the chosen independent variables in explaining changes in the dependent variable. These findings indicate the favourable attitude of stakeholders towards digital agricultural communication and services, laying a strong foundation for advancing digitalization in agriculture. This could enhance information dissemination and service improvements in the agricultural ecosystem.